PENGARUH MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI LQ45 - Etyka Saelandri; Olivia Niantari; Putri Amulia; Via Ayu Pujilestari; Ardyan Firdausi Mustoffa (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
Profit management is all activities carried out by managers to influence profits in accordance with their goals. The goal of earnings management is to increase the welfare of certain parties, although there is no difference between the company's cumulative profit and profits that can be introduced as an advantage in the long term. long. Meanwhile, company value is an investor's view of manager success in managing resources related to the company's stock price (Silvia Indrarini, 2019). Earnings management also affects the value of a company, but only for a certain period and does not increase the value of the company over a long period of time. This happens because earnings management is an activity that changes both reducing and adding data to financial reports. In this study, researchers used a Literature Study that was sourced from relevant theories and previous research journals. From the research results it is known that the company's value is influenced by earnings management and has varied results on the value of a company.